Double Trouble: Visual and Phonological Impairments in English Dyslexic Readers - Provazza, Serena; Adams, Anne-Marie; Giofrè, David; Roberts, Daniel John (Frontiers in Psychology, 2019)
Developmental dyslexia is a reading disorder characterized by problems in accurate or fluent reading. A deficiency in phonological processing is thought to underpin the reading difficulties of individuals with developmental dyslexia and a variety of explanations have been proposed including deficits to phonological awareness and verbal memory. Recent investigations have begun to suggest that developmental deficits in the acquisition of reading may also co-occur with visual processing deficits, which are particularly salient for visually complex stimuli, yet these deficits have received relatively little attention from researchers. To further explore the nature of phonological and visual processing in developmental dyslexia, we administered a series of non-reading tasks tapping both domains. Unsurprisingly, individuals with developmental dyslexia performed worse than typically developing readers in phonological tasks. More intriguingly, they also struggled with visual tasks, specifically when discriminating between novel visual patterns, and in visuo-spatial working memory which requires greater attentional control. These findings highlight that individuals with developmental dyslexia present not only with phonological impairments but also difficulties in processing visual materials. This aspect has received limited attention in previous literature and represents an aspect of novelty of this study. The dual phonological and visual impairments suggest that developmental dyslexia is a complex disorder characterized by deficits in different cognitive mechanisms that underpin reading.